2018
DOI: 10.1128/mcb.00678-17
|View full text |Cite
|
Sign up to set email alerts
|

P-Body Localization of the Hrr25/Casein Kinase 1 Protein Kinase Is Required for the Completion of Meiosis

Abstract: P-bodies are liquid droplet-like compartments that lack a limiting membrane and are present in many eukaryotic cells. These structures contain specific sets of proteins and mRNAs at concentrations higher than that in the surrounding environment. Although highly conserved, the normal physiological roles of these ribonucleoprotein (RNP) granules remain poorly defined. Here, we report that P-bodies are required for the efficient completion of meiosis in the budding yeast P-bodies were found to be present during a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
18
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 66 publications
0
18
0
Order By: Relevance
“…CK1δ and its ortholog Hrr25 have been detected within P-bodies, cytoplasmic RNA-protein granules present in meiotic cells. This binding seems to reduce CK1 turnover into the cytoplasm, thereby preserving protein integrity for subsequent stages of meiosis (Zhang et al, 2016;Zhang et al, 2018). Localization of Hrr25 to P-bodies is necessary for completion of the meiotic program (Zhang et al, 2018).…”
Section: Ck1δ In Cell Cycle Mitosis and Meiosismentioning
confidence: 99%
See 1 more Smart Citation
“…CK1δ and its ortholog Hrr25 have been detected within P-bodies, cytoplasmic RNA-protein granules present in meiotic cells. This binding seems to reduce CK1 turnover into the cytoplasm, thereby preserving protein integrity for subsequent stages of meiosis (Zhang et al, 2016;Zhang et al, 2018). Localization of Hrr25 to P-bodies is necessary for completion of the meiotic program (Zhang et al, 2018).…”
Section: Ck1δ In Cell Cycle Mitosis and Meiosismentioning
confidence: 99%
“…This binding seems to reduce CK1 turnover into the cytoplasm, thereby preserving protein integrity for subsequent stages of meiosis (Zhang et al, 2016;Zhang et al, 2018). Localization of Hrr25 to P-bodies is necessary for completion of the meiotic program (Zhang et al, 2018). Hrr25 has also been observed to be involved in the induction of nuclear division of meiosis as well as in the synthesis of membranes to engulf newly synthetized nuclei, thereby mediating the exit from meiosis II (Arguello-Miranda et al, 2017).…”
Section: Ck1δ In Cell Cycle Mitosis and Meiosismentioning
confidence: 99%
“…Yck3 is a vacuolar membrane-localized kinase that mediates vacuolar membrane fusion (LAGRASSA AND UNGERMANN 2005; ZICK AND WICKNER 2012;LAWRENCE et al 2014). Hrr25 is implicated in multiple cellular processes, including vesicular trafficking, ribosome biogenesis, autophagy, transcriptional regulation, meiosis, endocytosis, microtubule assembly and spindle positioning, and DNA damage response (HOEKSTRA et al 1991;PETRONCZKI et al 2006;SCHAFER et al 2006;RAY et al 2008;MEHLGARTEN et al 2009; CORBETT AND HARRISON 2012;SARKAR et al 2013;MOCHIDA et al 2014;PFAFFENWIMMER et al 2014;TANAKA et al 2014;ABDEL-FATTAH et al 2015;GHALEI et al 2015;NAKATOGAWA 2015;PENG et al 2015a;PENG et al 2015b;DAVIS et al 2016;ARGUELLO-MIRANDA et al 2017;COLLINS et al 2017;ZHANG et al 2018;ZIENTARA-RYTTER et al 2018;NEMEC et al 2019). The kinase domains of these four casein kinase I isoforms are highly similar, while the sequences outside the kinase domain are not conserved (WANG et al 1996;GROSS AND ANDERSON 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Consistent with its multiple cellular functions, Hrr25 is localized to different cellular locations, including endocytic sites, bud neck, P-bodies, spindle pole bodies, and the nucleus (PENG et al 2015a;PENG et al 2015b;ZHANG et al 2016). Hrr25 has an N-terminal kinase domain, a middle region, and a C-terminal P/Q rich region (DHILLON AND HOEKSTRA 1994;PENG et al 2015a;PENG et al 2015b;YE et al 2016;ZHANG et al 2016;ZHANG et al 2018). The middle region has been proposed or shown to be required for Hrr25's localization to P-bodies, spindle pole bodies, endocytic sites, and meiosis I centromeres.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the presence in SGs of regulators of a stress-responsive MAPK pathway determines whether cells undergo apoptosis in response to certain stresses (Arimoto et al 2008). In addition, the recruitment of the budding yeast CK1 protein kinase Hrr25 to the P-body has been shown to be important for the efficient completion of meiosis (Zhang et al 2018). As a result of these types of studies, it has been suggested that these RNP granules might play a role in the reprograming of specific signaling networks in response to stress (Kedersha et al 2013;Shah et al 2014).…”
mentioning
confidence: 99%